2008
DOI: 10.1002/jgm.1208
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thoracic gene delivery by magnetic nanobead‐mediated vector

Abstract: MNB-mediated gene delivery could comprise a promising method for gene delivery to the lung and the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 54 publications
4
46
0
Order By: Relevance
“…Li et al optimized the conjugation of PEI onto the surface of the magnetic nanoparticles. The magnetic nanoparticles could enhance the transfection efficiency and effectively deliver genes to the left side of the mouse thorax underexternal magnetic guidance (Li et al 2007b(Li et al , 2008.…”
Section: Applications For Therapeutic Devicesmentioning
confidence: 99%
“…Li et al optimized the conjugation of PEI onto the surface of the magnetic nanoparticles. The magnetic nanoparticles could enhance the transfection efficiency and effectively deliver genes to the left side of the mouse thorax underexternal magnetic guidance (Li et al 2007b(Li et al , 2008.…”
Section: Applications For Therapeutic Devicesmentioning
confidence: 99%
“…Under general anesthesia, after the placement of a 20g intravenous catheter into the distal cephalic vein, for the forearm, or into the small saphenous vein, for the hind limb, a tourniquet, above the elbow or the knee, is inflated to a pressure of 450 mmHg. The gene solution is rapidly infusion at a rate of 2 ml/sec and 2 minutes post-injection the tourniquet is deflated 55,72,73,30,31,32 .…”
Section: Primatesmentioning
confidence: 99%
“…Li et al (56) reported that transfection efficiency of PEI/DNA polyplexes, which are covalently linked to dextran-modified magnetic beads (200 nm), shows 35- to 85-fold higher values under magnetic field. Similarly, Xenariou et al (57) demonstrated reporter gene expression of Lipofectamine 2000/pDNA lipoplex increase 300-fold under a magnetic field, when complexed with TransMAG PEI (consisting of iron oxide cores and PEI shell) at suboptimal pDNA concentrations.…”
Section: Nanomagnets In Nanomedicinementioning
confidence: 99%